ROLE OF FIGURATIVE LANGUAGE IN CONTEMPORARY ADVERTISING (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: Advertising is an integral part of our time, it is one of the most effective ways to present a product or service to consumers. Advertising aims to attract consumers, attract their attention and encourage them to buy a product. The role of figurative language in modern advertising is very important, because figurative language is one of the main means of advertising. It further enriches the content of advertising, affects the emotions of consumers and emphasizes the uniqueness of the product.